An Overview of Project Delivery Methods in Construction Industry - S. Z Syed Zuber; M. N. Mohd Nawi; F.A. Abdul Nifa; A. Y. Bahaudin (International Journal of Supply Chain Management, 2018)
The selection of project delivery method is one of the factors that can influence the success of a construction project. Therefore, understanding each of the primary project delivery methods used in construction industry; Design-Bid-Build (DBB), Construction Manager at Risk (CM at Risk) and Design-Build (DB) are important before the decision-making. This paper is a theory based and the objectives are to develop a new definition of project delivery method by synthesizing the existing definitions and to describe the project delivery methods aforementioned. Their advantages, disadvantages and comparison in terms of delivery phase and performance are also presented. There is no project delivery method that appropriate to be used for any construction project therefore, the development of new ideal methods is important to achieve a successful construction project.